Cumulative disadvantage? The role of race compared to ethnicity, religion, and non-white phenotype in explaining hiring discrimination in the U.S. labour market - Ruta Yemane (Research in Social Stratification and Mobility, 2020)
Numerous correspondence studies have found strong and persistent evidence for racial discrimination in the U.S. labour market. However, since in the majority of studies race was the only variable that was manipulated, it is difficult to disentangle whether it is the ethnic background, the phenotype, the religious affiliation, or a combination of all that drives hiring discrimination. To answer this question, I draw on the theoretical framework of intersectionality and look at the role of ethnicity, as well as religion and non-white phenotype, and how they mediate discrimination outcomes using data from a correspondence study that was conducted across 49 states in the U.S. (N=2,107). The results show that next to racial preferences, employers also have ethnic preferences that influence their hiring decisions. In addition, I find significant evidence for an anti-Muslim bias which is stronger for phenotypical whites than for phenotypical non-whites. Although the overall penalty for applicants who are ascribed non-whites and who additionally have a Muslim affiliation is higher in magnitude, the penalty is not statistically different from the penalty of either being non-white or having a Muslim religious affiliation only. This result is not in line with intersectional theory and suggests that for some employers, one signal of otherness (either non-whiteness or Muslim religious affiliation) is enough to elicit strong bias.
Keywords: 300; race and ethnicity; religion; phenotype; intersectionality; hiring discrimination